High-Resolution Dynamics of Hydrogen Peroxide on the Surface of Scleractinian Corals in Relation to Photosynthesis and Feeding - Ousley, Sara; de Beer, Dirk; Bejarano, Sonia; Chennu, Arjun (Frontiers in Marine Science, 2022)
We developed and used a microsensor to measure fast (<1 s) dynamics of hydrogen peroxide (H2O2) on the polyp tissue of two scleractinian coral species (Stylophora pistillata & Pocillopora damicornis) under manipulations of illumination, photosynthesis and feeding activity. Our real-time tracking of H2O2 concentrations on the coral tissue revealed rapid changes with peaks of up to 60 µM. We observed bursts of H2O2 release, lasting seconds to minutes, with rapid increase and decrease of surficial H2O2 levels at rates up to 15 µM s-1. We found that the H2O2 levels on the polyp surface are enhanced by oxygenic photosynthesis and feeding, whereas H2O2 bursts occurred randomly, independently from photosynthesis. Feeding resulted in a 3-fold increase of baseline H2O2 levels and was accompanied by H2O2 bursts, suggesting that the coral host is the source of the bursts. Our study reveals that H2O2 levels at the surface of coral polyps are much higher and more dynamic than previously reported, and that bursts are a regular feature of the H2O2 dynamics in the coral holobiont.